Editorial - Bhalalusesa, Eustella (Papers in Education and Development, 2024)
Dear readers, Welcome to Volume 42, Supplementary Issue (December 2024) of Papers in Education and Development (PED). This edition presents a thought-provoking collection of research exploring strategies to enhance educational outcomes across various African contexts. The issue comprises eleven articles, each addressing critical dimensions of education, with a shared focus on improving quality and meeting the unique needs of educators and learners alike. Collectively, the findings offer profound insights into the interplay between theory and practice, underscoring the pivotal role of education systems in addressing societal and pedagogical challenges.